Implementation Of Traditional Market Management Policy In North Keputran Market, Surabaya City - Libragiantari, Elvira Dewanti; Wibawani, Sri (UNIVERSITAS PAKUAN, 2020)
This study aims to analyze the implementation of people's market management policies in North Keputran Market, Surabaya in realizing a clean, safe, comfortable, and fair market. Using the George C. Edward III policy implementation model, this study evaluates four key variables: communication, resources, disposition, and bureaucratic structure. The method used is qualitative descriptive with data collection techniques through interviews, observations, and document analysis. The results show that despite efforts to implement policies, there are still challenges in terms of communication, resource allocation, and bureaucratic coordination. The conclusion of this study is that the achievement of a clean, safe, comfortable, and fair market still faces obstacles, so more consistent policy enforcement and better resource management are needed.